High School Girl's Adherence to 5-a-Day Serving's Fruits and Vegetables: An Application Theory of Planned Behavior - Babak Moeini; Malihe Taheri; Ghodratolah Roshanaei; Ali Asghar Vahidinia; Masome Rostami moez (Journal of Education and Community Health)
Introduction: One of the basics of healthy eating is five times consumption of fruits and vegetable a day. Given the importance of recognizing effective factors of consuming fruit and vegetable in this group, the present study aimed to investigate high school girl's adherence to five-time serving fruits and vegetables per day in Hamadan based on the theory of planned behavior application. Materials and Methods: This descriptive-analytical study was performed on 400 girl students from high schools of Hamadan recruited with a multistage cluster sampling method. Participants filled out questionnaires including demographic variables, the theory of planned behavior constructs and a fruit and vegetable consumption measure one week later. Data analysis was performed using SPSS-18 by Chi-square, Pearson correlation and Logistic regression. Results: Fruit and vegetable consumption by female students is 3.4 times daily. Among the demographic variables, family size, mother's education, father's occupation, household income, body mass index and type of school had significant associations with fruit and vegetable consumption (P<0.05). Behavioral intention predicted 35% of the variation in daily fruit and vegetable consumption. Moreover, subjective norms, perceived behavioral control and attitude were able to predict 32% of behavioral intention. Conclusion: Fruit and vegetable consumption in female students is inadequate. The theory of planned behavior may be a useful framework to design a 5-A-Day intervention for female students.